Development of A Virtual Laboratory for Electrochem to Support Students' Critical Thinking Skills - M Rizki; Rayandra Asyhar; Isra Miharti; Zurweni; Firdiawan Ekaputra (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The application of interactive learning media plays an important role in stimulating motivation and deepening students' understanding, especially in bridging the characteristics of abstract chemistry learning, one of which is the material of electrolyte and non-electrolyte solutions. The main problem in chemistry learning in Madrasah Aliyah is the limited physical laboratory facilities, which impacts the low critical thinking skills of students. This study aims to develop a Virtual Laboratory "Electrochem Lab" that supports critical thinking skills and to test its feasibility conceptually and practically. As a supporting instrument, Electrochem Lab is equipped with an evaluation feature in the form of a quiz consisting of 5 questions based on Higher Order Thinking Skills (HOTS) that have been adjusted to train students' critical thinking skills independently. The study adopts a Research and Development (R&D) framework, specifically following the Lee & Owens model, which progresses through phases of analysis, design, development, implementation, and evaluation. The experimental subjects involved two experts (materials and media), one chemistry teacher, and 13 students of grade XI IPA MAN 5 Batang Hari consisting of 3 students in one-to-one tests with heterogeneous cognitive representations and 10 students in small group tests. The data collection instrument used a Likert Scale questionnaire consisting of a media expert questionnaire and a material expert questionnaire, a student response questionnaire and a one-to-one trial instrument. Evidence of the validity of the instrument and product was obtained through expert assessments stating that the media was very suitable for testing. The results showed a feasibility percentage of 90% from media experts and 89.23% from material experts, both of which were considered very suitable. The practitioner's assessment (chemistry teacher) reached 94.55%, while the one-to-one test reached 86,6% and the small group trials reached 98% with a very good category. It can be concluded that the Android-based virtual laboratory "Electrochem Lab" is very suitable to be used as an innovative solution to bridge the understanding of abstract concepts through sub-microscopic visualization and support the training of students' critical thinking skills. The novelty of this research lies in the integration of a contextual approach in digital simulations that connect learning materials with the students' surroundings and the Madrasah Aliyah environment.